Family and Relationship Services Economic Evaluation - Lacey, Sarina; McCarthy, Dennis; Berry, Tomas (Family and Relationship Services Australia, 2023)
The CIE was commissioned by Family and Relationship Services Australia to use cost benefit analysis to estimate the net social and economic benefits of a wide range of Family and Relationship Services available to Australians funded by the Department of Social Services (DSS) and the Attorney Generals Department. Based on extensive analysis of prior studies and new evidence, we estimate that Family Law Services return $7.85 in benefits for each dollar in invested, and services funded by DSS under the Families and Childrens Activity return $8.67 for every dollar invested. These very strong returns are mainly achieved as a result of: significant improvements in client wellbeing, particularly in mental health and personal and family safety; significant improvements in age-appropriate development and family functioning, leading to lifelong impacts on education, employment, mental health, and justice sector outcomes, and; avoided court costs for government and individuals as most clients participating in Family Dispute Resolution and similar services are diverted from court.
Keywords: Adolescents and youth; Childhood and child development; Families and relationships; Government, law and policy; Health and wellbeing; Housing, communities and neighbourhoods